2021
DOI: 10.2196/26098
|View full text |Cite
|
Sign up to set email alerts
|

The Value of Mobile Health in Improving Breastfeeding Outcomes Among Perinatal or Postpartum Women: Systematic Review and Meta-analysis of Randomized Controlled Trials

Abstract: Background Breastfeeding is essential for maintaining the health of mothers and babies. Breastfeeding can reduce the infection rate and mortality in newborns, and can reduce the chances of overweight and obesity in children and adolescents. For mothers, a longer duration of breastfeeding can reduce the risk of breast cancer, ovarian cancer, and type 2 diabetes. Although breastfeeding has many benefits, the global breastfeeding rate is low. With the progress of time, the popularity of mobile devices… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(23 citation statements)
references
References 24 publications
1
22
0
Order By: Relevance
“…Research into the development and testing of evidence‐based mHealth interventions for breastfeeding is growing. A recent systematic review and meta‐analysis (Qian et al, 2021) of 15 randomised controlled trials (RCT) of mHealth breastfeeding interventions found that these interventions significantly increased exclusive breastfeeding rates at 1, 2, 3 and 6 months post‐partum and improved breastfeeding self‐efficacy, though not breastfeeding attitudes. Nearly half ( n = 7) of these studies were in low‐ to middle‐income countries: most used SMS and/or telephone support as the main delivery mode, two used web‐based interventions, and none used a mobile phone app.…”
Section: Introductionmentioning
confidence: 99%
“…Research into the development and testing of evidence‐based mHealth interventions for breastfeeding is growing. A recent systematic review and meta‐analysis (Qian et al, 2021) of 15 randomised controlled trials (RCT) of mHealth breastfeeding interventions found that these interventions significantly increased exclusive breastfeeding rates at 1, 2, 3 and 6 months post‐partum and improved breastfeeding self‐efficacy, though not breastfeeding attitudes. Nearly half ( n = 7) of these studies were in low‐ to middle‐income countries: most used SMS and/or telephone support as the main delivery mode, two used web‐based interventions, and none used a mobile phone app.…”
Section: Introductionmentioning
confidence: 99%
“…Their usage, and mHealth in particular, could transform health systems especially when technological and regulatory challenges are addressed (Alsswey et al, 2021 ; Elden et al, 2022 ). Global evidence shows that mHealth interventions significantly improves exclusive breastfeeding (Alnasser et al, 2018 ; Qian et al, 2021 ). Given the widespread use of mobile phone, further intervention research on using mHealth to promote exclusive breastfeeding in the region is needed to determine how best they can be used to promote breastfeeding.…”
Section: Discussionmentioning
confidence: 99%
“…Internet-based prenatal educational programs are found to be effective in alleviating maternal postpartum depression (16). Studies also showed that using mobile devices for health purposes can significantly improve the rate of exclusive breastfeeding, breastfeeding efficacy, and women's attitudes toward breastfeeding and reduce health problems in infants (17). As an example, Hui et al (2021) evaluated the effect of remote prenatal education on the breastfeeding rate and prenatal program participation of pregnant women in rural and remote communities of northern Canada.…”
Section: Dear Editormentioning
confidence: 99%